FEATURES OF THE INVESTIGATION OF CRIMES OF THEFT OF OTHERS’ PROPERTY COMMITTED WITH THE HELP OF INFORMATION TECHNOLOGY (Western European Journal of Linguistics and Education, 2024)
The article highlights the features of interrogation of the victim and suspect, which are considered the most important investigative actions in the investigation of crimes related to the theft of other people's property using information technology. Opinions were also expressed on other investigative actions aimed at improving the quality of crime investigations.